Job scheduling strategies for parallel processing : 21st International Workshop, JSSPP 2017, Orlando, FL, USA, June 2, 2017, Revised selected papers /: 21st International Workshop, JSSPP 2017, Orlando, FL, USA, June 2, 2017, Revised selected papers. (2018) - Unknown
No abstract available